Preferensi dan Willingness To Pay Wisatawan Terhadap Virtual Reality di Malang Night Paradise Pascapandemi - Aisyah Nur Azizah; Eko Ruddy Cahyadi (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The Covid-19 pandemic caused a decrease in the number of tourist visits and state revenue in the Indonesian tourism sector was 20.7 billion. The tourism sector's contribution to Indonesia's GDP in 2021 was only 4.2% and before the pandemic was 4.7%. Virtual Reality (VR) is an option for traveling during a pandemic. This study aims to analyze the characteristics of tourists, willingness to pay, and the factors that influence the willingness to pay of tourists on the use of VR. The sample of this study was 115 respondents who had visited Malang Night Paradise and were interested in using VR in Adventure Land. Data were analysed by using descriptive analysis, Contingent Valuation Method (CVM): bidding games & open-ended method, and multiple linear regression. The results showed that the characteristics of tourists were dominated by young people. The maximum price that respondents are willing to pay is IDR 26,772/ticket and the optimal price is IDR 19,295/ticket. This price is lower than the current ticket price, which is IDR 20,000. The factors that have a positive/negative and significant effect on the value of WTP are education, monthly income/pocket money, gender, and marital status. Therefore, companies can focus on increasing product and marketing innovation. Keywords: contingent valuation method, preference, regression, virtual reality, willingness to pay